Demand response program studies based on Singapore Electricity Market - Xu, Hua (2016)
The National Electricity Market of Singapore (NEMS) is well known for its maturity. And now Singapore is planning to incorporate a demand response (DR) program into NEMS, with the purpose of further improving the competitiveness and efficiency of the electricity market. This report provides an in-depth study on the DR program which incorporates demand side bidding and incentive payment. The current market clearing model (MCM) of Singapore’s wholesale electricity market is firstly introduced and a mathematical model on MCM is developed to simulate the current market clearing process, where the energy and ancillary services are determined simultaneously through a form of auction pricing. Secondly, the methodology of incorporating the demand side bidding is discussed, emphasizing on the newly introduced constraints and demand side offers. The current MCM is then modified accordingly. Thirdly, the mechanism of incentive payment, with the intention of promoting participation of DR, is explained. Numerical analysis and various case studies are performed to demonstrate how the current MCM and modified MCM with DR work. And the economic benefits of DR participation are also calculated and explained.